2013
DOI: 10.3892/ol.2013.1442
|View full text |Cite
|
Sign up to set email alerts
|

-216G/T (rs712829), a functional variant of the EGFR promoter, is associated with the pleural metastasis of lung adenocarcinoma

Abstract: Numerous mutations and variants in the epidermal growth factor receptor (EGFR) gene have been demonstrated to be associated with the occurrence, metastasis and prognosis of various types of tumors, including lung cancer. Thus, the present study aimed to investigate whether -216G/T (rs712829), a functional polymorphism of the EGFR promoter that is able to induce EGFR activation and overexpression, is associated with the pleural metastasis of lung adenocarcinoma. The study subjects were comprised of 326 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Interestingly, when comparing adenocarcinomas with known driver mutation, it is evident that adenocarcinomas with EML4-ALK1 rearrangement have a higher propensity for pleura metastasis and malignant effusion [ 124 ]. In one study, it was proposed that the 216G/T polymorphism of the EGF receptor may play a role in pleural metastasis by overexpressing the protein [ 125 ].…”
Section: Creating the Distant Metastatic Focusmentioning
confidence: 99%
“…Interestingly, when comparing adenocarcinomas with known driver mutation, it is evident that adenocarcinomas with EML4-ALK1 rearrangement have a higher propensity for pleura metastasis and malignant effusion [ 124 ]. In one study, it was proposed that the 216G/T polymorphism of the EGF receptor may play a role in pleural metastasis by overexpressing the protein [ 125 ].…”
Section: Creating the Distant Metastatic Focusmentioning
confidence: 99%
“…The epidermal growth factor receptor (EGFR) is involved in human tumors by regulating important cellular processes (Guo et al, 2013). Previous studies have reported singlenucleotide polymorphisms (SNPs) in the EGFR gene to be associated with several kinds of cancers, including lung cancer (He et al, 2013), breast cancer (Connor et al, 2013), and esophageal cancer (Lee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a significant association was also found between rs712829 and the risk of lung cancer of the adenocarcinoma subtype. A previous study reported an association between the rs712829 TT genotype and the pleural metastasis of lung adenocarcinoma in the Chinese population [26]. In addition, a lack of association between the rs712829 SNP and lung cancer was reported in a United States population [18] and a Japanese population [19].…”
Section: Discussionmentioning
confidence: 96%